2006
DOI: 10.1111/j.1540-8159.2006.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Right Ventricular Pacing in Patients with Dual‐Chamber ICDs

Abstract: AVSH can dramatically reduce the percentage of RV pacing among ICD recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In another randomized, crossover study in unselected pacemaker recipients, ventricular pacing was decreased from a median of nearly 90% in DDD mode, to less than 2% in the managed ventricular pacing mode through a 1‐month follow‐up period 24 . A third randomized trial compared VVI versus DDD pacing with AV search hysteresis in a population of ICD recipients and showed a moderated reduction in mean ventricular pacing while extending AV delay extension to 100% 25 . In the present study, we demonstrated a significant reduction in mean ventricular pacing in SafeR (3.4 ± 12.6%) as compared to both DDD modes at 2 months follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…In another randomized, crossover study in unselected pacemaker recipients, ventricular pacing was decreased from a median of nearly 90% in DDD mode, to less than 2% in the managed ventricular pacing mode through a 1‐month follow‐up period 24 . A third randomized trial compared VVI versus DDD pacing with AV search hysteresis in a population of ICD recipients and showed a moderated reduction in mean ventricular pacing while extending AV delay extension to 100% 25 . In the present study, we demonstrated a significant reduction in mean ventricular pacing in SafeR (3.4 ± 12.6%) as compared to both DDD modes at 2 months follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective analysis examined all INTRINSIC RV trial subjects with age documented in the database. Methods and results have been reported previously [10]. Enrolled patients provided informed consent prior to ICD implantation.…”
Section: Methodsmentioning
confidence: 99%
“…8 If the right ventricle was paced Ͼ20% of the time, the patient was not randomized but rather was placed in an observational arm. The protocol specified a 12-month follow-up period with an actual mean of 10.4 months.…”
Section: Methodsmentioning
confidence: 99%